2022
DOI: 10.3390/antibiotics11070835
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Carbapenem-Resistant Acinetobacter baumannii Isolated from Intensive Care Unit Patients in Jordanian Hospitals

Abstract: Acinetobacter baumannii is a common cause of healthcare-associated infections (HAI) worldwide, mostly occurring in intensive care units (ICUs). Extended-spectrum beta lactamases (ESBL)-positive A. baumannii strains have emerged as highly resistant to most currently used antimicrobial agents, including carbapenems. The most common mechanism for carbapenem resistance in this species is β-lactamase-mediated resistance. Carbapenem-hydrolyzing class D oxacillinases are widespread among multidrug-resistant (MDR) A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similar findings were recently reported demonstrating the involvement of bla OXA gene in mediating resistance to cephalosporins. 27 Analysis of bla CTMX, bla TEM, and bla SHV genes revealed a high resistance gene carriage in more than 50% of studied isolates. High prevalence of these markers had been reported previously in an Indonesian hospital.…”
Section: Discussionmentioning
confidence: 91%
“…Similar findings were recently reported demonstrating the involvement of bla OXA gene in mediating resistance to cephalosporins. 27 Analysis of bla CTMX, bla TEM, and bla SHV genes revealed a high resistance gene carriage in more than 50% of studied isolates. High prevalence of these markers had been reported previously in an Indonesian hospital.…”
Section: Discussionmentioning
confidence: 91%
“…In recent years A. baumannii research in Jordan has focused on its phenotypic and genotypic resistance profiles, the mechanism of drug resistance and clinical epidemiology with little attention on the mechanism of virulence and pathogenesis [25,32,33]. In this research, molecular and conventional assays were conducted to inspect the virulence genes harbored in CRAB strains isolated from clinical samples in two hospitals in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the abuse of antibiotics, A baumannii was resistant to multiple antibiotics, named “Multiple Resistance Acinetobacter Baumannii .” [18] A baumannii infection could result in death in an intensive unit. [19–23]…”
Section: Discussionmentioning
confidence: 99%
“…[18] A baumannii infection could result in death in an intensive unit. [19][20][21][22][23] Finally, it was found that the patients who suffered from death got higher rates of usage of continuous renal replacement therapy and mechanical ventilation. Patients who needed the treatment of continuous renal replacement therapy or mechanical ventilation usually suffered from severe forms of AP.…”
Section: Discussionmentioning
confidence: 99%